Unconditional and conditional QTL underlying the genetic interrelationships between soybean seed isoflavone, and protein or oil contents. Issue 3 (8th April 2015) - Han, Yingpeng; Teng, Weili; Wang, Yan; Zhao, Xue; Wu, Lin; Li, Dongmei; Li, Wenbin; Morris, B.
Abstract Selection for soybean (Glycine max L. Merr.) rich in isoflavones, protein and oil has been difficult due to negative genetic interrelationships. In this study, genetic interrelationships among seed isoflavones and protein and oil contents were evaluated using both unconditional and conditional QTL mapping. Daidzein (DZ), genistein (GT), glycitein (GC) and total isoflavone (TI) contents were analysed in F5:6, F5:7 and F5:8 recombinant inbred lines (RILs) derived from a cross between 'Zhongdou 27'(TI 3791 μg/g; protein content 42.84%; oil content 18.73%) and 'Jiunong 20' (TI 2061 μg/g; protein content 34.05%; oil content 21.42%). When DZ, GT, GC and TI were analysed for their genetic relationships with protein or oil contents, eight conditional QTL were detected, which included DZ|pro, GC|pro, GT|pro, TI|pro, DZ|oil, GC|oil, GT|oil and TI|oil. Seventeen QTL that had significant genetic associations between seed isoflavone, and seed protein or oil contents were found, including two for DZ conditioned on protein (qDZ|proK‐1, qDZ|proF‐2); one for GC conditioned on protein (qGC|proM‐1); three for GT conditioned on protein (qGT|proM‐1, qGT|proA2‐1, qGT|proL‐1); three for TI conditioned on protein (qTI|proM‐1, qTI|proA2‐1, qTI|proF‐2); one for DZ conditioned on oil (qDZ∣oil K_1); one for GC conditioned on oil (qGC∣oilI_1); four for GT conditioned on oil (qGT∣oil A2_1, qGT∣oil F_1, qGTF_2, qGT∣oilD2_1); three for TI conditioned on oil (qTI∣oilA2‐1, qTI∣oilE‐1, qTI∣oilL‐1). Few epistatic interactions among loci were detected. These loci may be valuable for improving seed isoflavone, protein and oil contents.